1997
DOI: 10.1021/ja961446b
|View full text |Cite
|
Sign up to set email alerts
|

Iron L-Edge X-ray Absorption Spectroscopy of Myoglobin Complexes and Photolysis Products

Abstract: We demonstrate the first application of L-edge X-ray absorption spectroscopy (XAS) to the electronic characterization of biological photolysis products. The experimental L-edge XAS spectra of deoxymyoglobin (deoxy Mb), oxymyoglobin (MbO2), carbonmonoxymyoglobin (MbCO), and the low-temperature photoproducts (Mb*CO and Mb*O2) are presented and compared to simulated spectra using a ligand field multiplet calculation. This analysis indicates that MbCO and MbO2 are both low spin and does not support some previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 57 publications
7
75
1
Order By: Relevance
“…In a pioneering experiment, Mills and co-workers probed the reversible photodissociation of a CO group from carboxymioglobin via TR-XANES at the Fe K-edge [140,[234][235][236]. Similar studies on related systems were reported by Clozza et al [237] and by Chance and co-workers [141,[238][239][240]. In addition, Chen et al investigated the lightdriven redox processes in an Fe-Zn diporphyrin integrated in a modified haem protein [241].…”
Section: (Py) 2 ] 2+mentioning
confidence: 84%
See 1 more Smart Citation
“…In a pioneering experiment, Mills and co-workers probed the reversible photodissociation of a CO group from carboxymioglobin via TR-XANES at the Fe K-edge [140,[234][235][236]. Similar studies on related systems were reported by Clozza et al [237] and by Chance and co-workers [141,[238][239][240]. In addition, Chen et al investigated the lightdriven redox processes in an Fe-Zn diporphyrin integrated in a modified haem protein [241].…”
Section: (Py) 2 ] 2+mentioning
confidence: 84%
“…Initially, the time resolution of these studies was limited to the ms-ns range [139][140][141][142], except for one groundbreaking case [143].Theoretical and experimental critical issues had to be considered to extend the feasibility of time-resolved XAS characterization to the sub-ns time domain.…”
Section: X-ray Transient Absorption: Theoretical Background and Expermentioning
confidence: 99%
“…Both the LMCT model and the crystal field model have been applied to model Fe L-edge spectral shape. 44, 45 Arrio and co-workers have analyzed a number of cubic systems with CNligands bridging two transition metal sites. [41][42][43]46 It was found for the Cr sites of these compounds that the LMCT model could not reproduce the shape of the spectra, and the multiplet model was adapted to include the effects of MLCT, which successfully reproduced the spectral shapes.…”
Section: Introductionmentioning
confidence: 99%
“…1), X-ray absorption spectroscopy (XAS) is an important tool. [36][37][38] Soft X-ray spectroscopy at the L 2/3 -edges [39][40][41][42] can, by virtue of the dipole selection rules, directly probe the iron 3d orbitals which are not observable in optical spectroscopy owing to the strong p -p* (Soret) band. However, the L 2/3 -edges of iron are less sensitive to the geometric structure than the K-edge, for which bond length, angles and dihedrals may be extracted by the analysis of the spectral resonances occurring above the ionization potential in both the X-ray absorption near edge structure (XANES) and the extended X-ray absorption fine structure (EXAFS) regions, while the electronic structure is obtained via the pre-edge region of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…These attributes have led several groups to implement XAS for the study of heme proteins. 39,[43][44][45][46][47][48][49][50][51] Despite the fact that the physiological environment is the most relevant to the biological function, XAS studies of heme proteins under physiological conditions (pH 7 solution, room temperature and pressure) are almost completely lacking, except for the recent soft X-ray studies carried out at the Fe L 2/3 -edges. 40,42,52 Low temperature frozen solutions of heme proteins have generally been used as they reduce the thermal vibration of the atoms and, in the case of photolysed samples, trap intermediates so that their structures could be determined.…”
Section: Introductionmentioning
confidence: 99%